Implementasi Strategi Manajemen Supply Chain dalam Meningkatkan Kinerja Perusahaan (Literatur Review 2014-2024) - Nurnadia, Nurnadia; Kaseng, Saharuddin; Miru, Sulaeman; Hadi, Suryadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This research aims to analyze and synthesize findings from various empirical studies on the implementation of supply chain management (SCM) strategies and their impact on company performance in the 2014-2024 timeframe. This research uses the literature review method by collecting and analyzing relevant scientific articles from various sources, such as academic journals, conference proceedings, and research databases. The articles selected are empirical studies that directly discuss the implementation of SCM strategies and the measurement of company performance. The results of the literature review show that effective implementation of SCM strategies has a positive and significant impact on firm performance. SCM strategies that focus on increased collaboration with suppliers and customers, business process integration, efficient information sharing, and the use of information technology are proven to improve operational efficiency, reduce costs, improve product quality, speed up delivery times, and increase customer satisfaction. In addition, the research also highlights the importance of aligning SCM strategies with the company's overall business strategy to achieve optimal performance.